Study of carbohydrate, bioactive compounds, antioxidants, vitamin C, and mineral content at the ripening stage of grapes, rambutan, and pineapple: Study of biochemical and bioactive compounds in different fruits - Hossain, Abu Bakar Mohammad Sharif (Cellular and Molecular Biology, 2025)
The experiment was carried out to investigate the carbohydrate content as represented by glucose, fructose and sucrose, total soluble solids, carotenoid, flavonoid, antioxidant, phenolic content, pH, and minerals as micro-macro nutrient content in grapes, rambutan, and pineapple. A total of 50 fruits were collected for rambutan, five fruits from pineapple, and five bunches were collected for grapes in Experiment 1: Glucose content was higher in rambutan and pineapple than in grapes. The higher fructose content was found in rambutan than in grapes and pineapple. The highest sucrose was observed in rambutan. The highest total soluble solid (TSS) content was found in rambutan. Vitamin C and fiber content exhibited the highest value in pineapple. However, carotenoid was higher in grapes and pineapple than in rambutan. The maximum flavonoid was found in rambutan. In addition, total antioxidant and phenolic content were higher in pineapple and rambutan than in grapes. Potassium content was higher in grapes and pineapple compared to the rambutan, whereas phosphorus content was the highest in pineapple, and calcium content was the highest in rambutan. Mn, Fe, and Zn were found in higher amounts in rambutan than in pineapple and grapes. In Experiment 2: glucose, sucrose, and vitamin C decreased while fructose, TSS, pH, and biomass increased. In addition, moisture decreased with the increase of total antioxidant capacity (TAC) in grapes, rambutan and pineapple. Carotenoid content was highest in grapes, flavonoid was highest in rambutan and total phenol was highest in pineapple. Therefore, it can be concluded that grapes showed better mineral content, rambutan exhibited the highest sugar and flavonoid content, and pineapple showed the highest bioactive compounds.